1998
DOI: 10.1161/01.str.29.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Determinants of Poststroke Dementia

Abstract: Background and Purpose-Frequency of poststroke dementia is high, and stroke considerably increases the risk of dementia.The risk factors for dementia related to stroke are still incompletely understood. We sought to examine clinical determinants of poststroke dementia in a large well-defined stroke cohort. Methods-The study group comprised 337 of 486 consecutive patients aged 55 to 85 years who 3 months after ischemic stroke completed a comprehensive neuropsychological test battery and MRI, including structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
242
8
18

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(286 citation statements)
references
References 46 publications
18
242
8
18
Order By: Relevance
“…107 The main risk factors for white matter lesions are hypertension, particularly high systolic blood pressure, 101,108,109 although some authors have reported either no or an inverse association with blood pressure. 94,110,111 White matter lesions have also been associated with vascular risk factors including history of stroke, 105,110 heart disease, 105,110 atrial fibrillation 110 and diabetes mellitus. 112 The main hypothesis regarding the cause of white matter lesions is that long-standing hypertension may cause lipohyalinosis and thickening of the vessel walls with narrowing of the lumen of the small perforating arteries which could lead to ischaemia in the terminal distribution territories of these vessels, ie, deep white matter.…”
Section: Author Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…107 The main risk factors for white matter lesions are hypertension, particularly high systolic blood pressure, 101,108,109 although some authors have reported either no or an inverse association with blood pressure. 94,110,111 White matter lesions have also been associated with vascular risk factors including history of stroke, 105,110 heart disease, 105,110 atrial fibrillation 110 and diabetes mellitus. 112 The main hypothesis regarding the cause of white matter lesions is that long-standing hypertension may cause lipohyalinosis and thickening of the vessel walls with narrowing of the lumen of the small perforating arteries which could lead to ischaemia in the terminal distribution territories of these vessels, ie, deep white matter.…”
Section: Author Resultsmentioning
confidence: 99%
“…138,142,[144][145][146][147] Risk factors for post-stroke dementia At least three different groups of factors, each acting independently, rather than a single pathophysiological mechanism probably contribute to the development of post-stroke dementia: 111,148 (1) stroke-related factors such as the location and the severity of the brain lesions; 149,150 (2) the overall cardiovascular risk profile as determined by the presence of atrial fibrillation 140 or diabetes mellitus; 149 (3) non-strokerelated factors similar to those found in Alzheimer's disease including increasing age, 149,151 low education, 149 cortical atrophy. 145,152 Hypertension has been identified as a risk factor by Pohjasvaara et al (1998), 111 but not by Skoog et al (1996). 101 In addition to those risk factors, coexisting Alzheimer's disease pathology may also play a role, as indicated 146 9.6 Andersen et al, 1996 147 5.5 Kokmen et al, 1996 138 8.4 Hénon et al, 1997 144 16.3 Pohjaasvara et al, 1997 142 12.2…”
Section: Post-stroke Dementiamentioning
confidence: 99%
“…Controversy exists regarding the association of the ApoE⑀4 allele with VaD (Chapman et al, 1998;Marin et al, 1998), leading to the conclusion that ApoE is not a robust prognostic factor for this disease. In fact, despite its high incidence, no specific risk factors for VaD are known (Pohjasvaara et al, 1998). The distribution of ApoE polymorphisms was tested in a random subgroup of 75 patients (Table 1).…”
Section: Other Risk Factorsmentioning
confidence: 99%
“…The age and large artery stroke were observed to be significantly different in those patients. Our findings are in accordance with the results of previous works (Desmond et al., 2000; Patel, Coshall, Rudd, & Wolfe, 2002; Pohjasvaara et al., 1998; Rockwood, 2002). In contrast, Auperin et al.…”
Section: Discussionmentioning
confidence: 99%